NCOG-28. LEEDS LOW GRADE GLIOMA SERVICE 2010-2022: A 12-YEAR EXPERIENCE. (14th November 2022) - Kalra, Neeraj; Livermore, James; Spink, Suzanne; Boyer, Gillian; O'Malley, Lianne; Flatley, Michael; Maguire, Melissa; Fairclough, Sam; Wright, Elizabeth; Armstrong, Caroline; Stephenson, Elisa; Ewan, Seonaid; et al.
Abstract: INTRODUCTION: We present our 12-year experience of the surgical management of lower-grade gliomas (LGGs) by a multidisciplinary team in a large tertiary UK brain tumour centre. METHODS: Retrospective analysis of all adult patients who underwent surgery in the Leeds Low Grade Glioma Service between January 2010 and January 2022. Data collected included demographics, procedure type, extent of resection, histological diagnosis, morbidity, mortality, tumour location, seizure control, adjuvant therapy, cognitive outcomes, progression-free survival (PFS) and overall survival (OS). Results were statistically analysed by Kaplan-Meier and Log Rank (Cox Proportional Regression Hazard) Testing (p< 0.05). RESULTS: 254 patients underwent surgery between 2010-2022. Of these, 77 patients underwent a second resection surgery, 9 a third, and 1 patient had a total of 4 resections. 184 operations were carried out awake, 115 asleep and 42 patients underwent biopsy only. The most common histology at initial surgery was astrocytoma, IDH1m, WHO Grade 2 (41.7%) with oligodendroglioma, IDH1m, WHO Grade 2 being the second most common. The majority of tumors were located in the right frontal lobe (24%) followed by the left frontal lobe (18%). 32% of tumors were on the left side. The median time between diagnosis and first surgery was 36.5 months. 8 patients died during this time frame, 7 who had resection, 1 had biopsy. CONCLUSION: Our experience of the surgical management of LGG over the last 12 years shows that maximal safe surgical resection remains important as first-line treatment. Greater extent of resection (EOR) can delay transformation, control seizures and improve survival. Awake surgery is well tolerated and can preserve eloquent function. A multidisciplinary team approach achieves the best outcomes, and is appreciated by our patients